Undiagnosed Anemia after 9 years: Diamond-Blackfan (homozygous Variant c.140G>T; p.Gly47Val in ADA2 Gene) - Obeidi , Narges; Gharehdaghi1, Zeynab; Fathpour, GholamReza; Rostamipoor, Mohadeseh (Archives of Advances in Biosciences, 2024)
Context: Diamond-Blackfan anemia (DBA) is a rare autosomal recessive disorder characterized by erythroblastopenia and pure red cell aplasia. The condition typically results from an abnormality in a ribosomal protein gene. Case presentation: Cases of cytopenia have been linked to ADA2 deficiency caused by CECR1 mutations. In the current case study, a child presented with severe anemia requiring multiple RBC transfusions due to the condition going undiagnosed. After 8 years, the patient developed elevated ferritin levels, severe neutropenia, and a serious infection that complicated the clinical picture. Molecular analysis revealed homozygous variants (c.140G>T p.Gly47Val) in the ADA2 gene inherited from heterozygous parents. Conclusion: This case represents the first documented instance in Iran, highlighting the importance of screening for congenital defects in seemingly healthy couples, especially emphasizing the need for prenatal diagnosis (PND) using molecular methods and genetic sequencing.